Automatyzacja wizualizacji grafowej synonimów dla potrzeb dydaktyki języków obcych (na przykładzie przymiotników rosyjskich z prefiksem „без-”/„бес-”) - Dzienisiewicz, Daniel; Fedorushkov, Yury (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article presents methods for application of lexicographic data for the purposes of foreign language teaching and linguistic studies. The automated graph visualization technique is introduced. Both the retrieval and the visualization of linguistic data in form of directed graphs have been conducted with the use of available computer software. The material on which the above-mentioned operations have been performed comprises the group of Russian adjectives with без- / бес- prefixes and the synonymic chains initiated by them. The automated extraction with the use of regular expressions, the steps leading to the edition of the generated database and the import of the final data base into a visualization software are described in the article. The grammatical and semantic characteristics of the sample group of lexemes are not the focus of this article, although further analysis of the selected vocabulary units is planned to be conducted in future studies.